Multi-objective Hierarchic Memetic Solver for Inverse Parametric Problems - Gajda-Zagórska, Ewa; Smołka, Maciej; Schaefer, Robert; Pardo, David; Álvarez-Aramberri, Julen (Procedia computer science, 2015)
We propose a multi-objective approach for solving challenging inverse parametric problems. The objectives are misfits for several physical descriptions of a phenomenon under consideration, whereas their domain is a common set of admissible parameters. The resulting Pareto set, or parameters close to it, constitute various alternatives of minimizing individual misfits. A special type of selection applied to the memetic solution of the multi-objective problem narrows the set of alternatives to the ones that are sufficiently coherent. The proposed strategy is exemplified by solving a real-world engineering problem consisting of the magnetotelluric measurement inversion that leads to identification of oil deposits located about 3km under the Earth's surface, where two misfit functions are related to distinct frequencies of the electric and magnetic waves.